2020
DOI: 10.1111/1365-2664.13721
|View full text |Cite
|
Sign up to set email alerts
|

Collateral benefits of targeted supplementary feeding on demography and growth rate of a threatened population

Abstract: 1. Effective evidence-based conservation requires full quantification of the impacts of targeted management interventions on focal populations. Such impacts may extend beyond target individuals to also affect demographic rates of non-target conspecifics (e.g. different age classes). However, such collateral (i.e. unplanned) impacts are rarely evaluated despite their potential to substantially alter conservation outcomes. Subsequent management decisions may then be poorly informed or erroneous. 2. We used 15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Nevertheless, at face value, our estimates suggest that the intervention effects on juvenile survival were sufficient to reduce (but not prevent) population decrease. Previous analyses showed that the intervention also had substantial collateral benefits, by increasing adult survival probability and components of reproductive success (Fenn et al., 2020). Together, these results imply that the intervention successfully prevented a rapid population decline (Trask et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at face value, our estimates suggest that the intervention effects on juvenile survival were sufficient to reduce (but not prevent) population decrease. Previous analyses showed that the intervention also had substantial collateral benefits, by increasing adult survival probability and components of reproductive success (Fenn et al., 2020). Together, these results imply that the intervention successfully prevented a rapid population decline (Trask et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al, 2013;Toomey et al, 2016;Williams et al, 2020). To fulfil academic objectives, primary scientific papers were strategically published in British Ecological Society journals, targeted at general concept-led international audiences spanning pure and applied ecology (Journal of Animal Ecology: Reid et al, 2003aReid et al, † , 2003bReid et al, ‡ , 2004Reid et al, , 2006Reid et al, , 2008Reid et al, , 2010Trask et al, 2016Trask et al, † , 2017Journal of Applied Ecology: Reid et al, 2011;Trask et al, 2019;Fenn et al, 2020Fenn et al, , 2021; total >685 citations, Google Scholar October 2021, Elton prize ‡ winner, † highly commended). Yet, while these papers retained some system-specific context, the focus on general conceptual rather than system-specific impact (as required for these BES journals) meant that the full process of pure-applied integration and its application to chough conservation was not previously visible.…”
Section: Methodsmentioning
confidence: 99%
“…Such analyses are widely advocated, especially where formal experiments are impossible, but still relatively rarely implemented (Christie et al., 2019). We showed that adults that attended feeding sites had higher annual survival probabilities, and higher probabilities of successful reproduction, than adults occupying the same territories in previous years, while adults currently occupying other territories did not (Fenn et al., 2020). The estimated increases in adult survival were substantial and, alongside estimated moderate increases in nest success, were almost sufficient to maintain λ close to one and hence maintain population stability (Fenn et al., 2020).…”
Section: Research Phasesmentioning
confidence: 96%
See 2 more Smart Citations